Chronic hepatitis C course at elderly and therapeutic approach - M. V. Mayevskaya; M. A. Morozova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To discuss features of course of chronic hepatitis C virus infection at elderly, efficacy and safety of antiviral treatment of patients of this age group.Original positions. In every day clinical practice elderly patients with chronic hepatitis C are extremely rarely considered as candidates for antiviral treatment. Such therapeutic tacticsis is not always justified. At patients in the age of 65 and over chronic hepatitis C has more severe course, than at young patients, with more rapid progression of fibrosis and low level of alanine transaminase. Due to this liver cirrhosis (LC) at elderly patients is more frequent, than at younger subjects. In series of studies it was demonstrated, that elderly age is independent risk factor of development of both LC, and hepatocellular carcinoma. Expediency of prescription of antiviral therapy to elderly patients should be solved individually, taking into account patient’s activity and quality of life. To assess the stage of disease and degree of fibrosis methods, alternative to liver biopsy, are preferable. Before onset of treatment, additional investigation to establish severity of concomitant diseases and risk of their complications should be carried out. One of the basic problems during antiviral therapy is development of ribavirin-induced anemia that is especially dangerous at patients with cardio-vascular diseases. This complication requires careful monitoring of hemoglobin and hematocrit level during the whole period of treatment and, if necessary, decline of drug doses according to established algorithms.Conclusion. Elderly age is not an absolute contraindication for antiviral treatment. At solving a question of prescription of antiviral therapy for chronic hepatitis C to elderly patients it is necessary to represent clearly the balance of the possible harm and benefits as well as the probable consequences of treatment cancellation.